"We Kind of Met In‐Between": A Qualitative Analysis of Young Couples' Relationship Dynamics and Negotiations About Pregnancy Intentions. Issue 2 (5th May 2020) - Arteaga, Stephanie; Downey, Margaret Mary; Freihart, Bridget; Gómez, Anu Manchikanti
Abstract : CONTEXT: The literature on reproductive decision making often focuses on women and neglects the role of men and the importance of relationship context. Research with couples is vital to understanding joint decision making regarding having children at various stages of a couple's relationship and an individual's life course. METHODS: In‐depth, individual interviews were conducted with a socioeconomically, racially and ethnically diverse sample of 50 young heterosexual women and their male partners in northern California in 2015–2016. A dyadic, thematic analytic approach was used to examine whether and how prospective pregnancy intentions and current pregnancy desires are negotiated at the couple level, and how relationship dynamics influence any negotiation and decision‐making processes. RESULTS: Twenty‐three couples described engaging in joint pregnancy decision making, which required purposeful communication and, for some, compromise and acceptance. For nearly all of these couples, these processes led to aligned prospective pregnancy intentions, even when current pregnancy desires differed. The remaining 27 couples described individual pregnancy decision‐making processes; many respondents reported intentions that aligned with their partner's by happenstance, despite some respondents having avoided communicating their desires to their partner. Some of these couples faced relationship difficulties, including poor communication, leading some participants to misinterpret or be unaware of their partner's pregnancy intentions and desires. CONCLUSIONS: The relationship context is important in the formulation of prospective pregnancy intentions among young people. Counseling protocols, interventions and policies that attend to the complex factors that influence young couples' pregnancy decision making are needed to better help couples attain their reproductive goals.